Computer Simulation Shows the Effect of Communication on Day of Surgery Patient Flow. (26th June 2015) - Taaffe, Kevin; Fredendall, Lawrence; Huynh, Nathan; Franklin, Jennifer
Abstract: To improve patient flow in a surgical environment, practitioners and academicians often use process mapping and simulation as tools to evaluate and recommend changes. We used simulations to help staff visualize the effect of communication and coordination delays that occur on the day of surgery. Perioperative services staff participated in tabletop exercises in which they chose the delays that were most important to eliminate. Using a day‐of‐surgery computer simulation model, the elimination of delays was tested and the results were shared with the group. This exercise, repeated for multiple groups of staff, provided an understanding of not only the dynamic events taking place, but also how small communication delays can contribute to a significant loss in efficiency and the ability to provide timely care. Survey results confirmed these understandings.